Order flow imbalance effects on the German stock market - Michael Hanke; Michael Weigerding (Business Research, 2015)
Order flow imbalance refers to the difference between market buy and sell orders during a given period. This paper is the first study to examine effects of order flow imbalance on returns of stocks traded on the German Xetra trading system on a daily basis. In contrast to previous studies on other markets, we control for unobserved effects using a fixed-effects panel regression. For the concurrent (or conditional) relation between order imbalance and returns, our results confirm those of the literature. For the question of return predictability from past order imbalances (unconditional relation), our results are partly confirmatory. In addition, we provide evidence for size and liquidity effects and analyze changes in imbalance effects during the financial crisis.
Keywords: 650; Order imbalance; Return predictability; Panel regression